Mobilités quotidiennes et modes d’habiter dans le périurbain francilien - Patricia Sajous; Mariane Thébert; Hélène Nessi; Monica Coralli (Netcom)
In a research devoted to ways of periurban living (Aguilera et al, 2014), we have collected material to question 3 aspects : territory - technical networks (ICT, automotive) - daily mobility, based on statements of thirty-one households living in Paris suburb (Haute Vallée de Chevreuse, Brie Boisée, Carnelle Pays de France). Starting with the management of uncertainty and the role played by ICT in said issue, we found that ICT enables the individual to elect a double position to face uncertainty. ICT is a clear progress to face uncertainty of transport network, we outline that it also ensures flexibility in activity program. The conclusions of this first part led to open the spectrum and analyse ICT in suburban ways of living. ICT are not seen as the tool to manage temporal and spatial tension between distance and proximity, typical of suburban areas. Nevertheless, they go together with an improvement of territorial household appropriation. Their use still largely advisory is subject to the links that individuals develop with the territory and does not replace it. This technical appropriation does not prevent from assuming that ICT will ultimately play a territorial adapter role similar to the one played by automobile.